2023
DOI: 10.3389/fpsyt.2023.1074736
|View full text |Cite
|
Sign up to set email alerts
|

The current state of research for psychobiotics use in the management of psychiatric disorders–A systematic literature review

Abstract: The need to find new therapeutic interventions in patients diagnosed with psychiatric disorders is supported by the data suggesting high rates of relapse, chronic evolution, therapeutic resistance, or lack of adherence and disability. The use of pre-, pro-, or synbiotics as add-ons in the therapeutic management of psychiatric disorders has been explored as a new way to augment the efficacy of psychotropics and to improve the chances for these patients to reach response or remission. This systematic literature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 86 publications
0
10
0
1
Order By: Relevance
“…No literature evidence has been found linking Selenomonadales to AD. However, it may be related to major depressive disorder (MDD) and Alzheimer's disease [38,39] . In previous studies on anxiety disorder cases, it has been found that individuals with AD have lower levels of Coprococcus [40] .…”
Section: Discussionmentioning
confidence: 99%
“…No literature evidence has been found linking Selenomonadales to AD. However, it may be related to major depressive disorder (MDD) and Alzheimer's disease [38,39] . In previous studies on anxiety disorder cases, it has been found that individuals with AD have lower levels of Coprococcus [40] .…”
Section: Discussionmentioning
confidence: 99%
“…These findings advocate for a personalized approach in psychobiotic administration and emphasize the necessity for targeted research to optimize these interventions, considering the heterogeneity in patient responses and specific biochemical pathways affected by different probiotic strains. Future research should focus on standardizing psychobiotic formulations and exploring their synergistic effects with conventional antidepressants to fully harness their therapeutic potential [14,24,96].…”
Section: Efficacy Of Psychobiotics In Treating Cognitive and Psychiat...mentioning
confidence: 99%
“…The results of these studies are detailed in articles focusing on specific probiotics, as well as in systematic reviews and meta-analyses [ 43 , 76 , 133 , 134 , 135 , 136 , 137 , 138 , 139 ]. This concept has given rise to the term ‘psychobiotics’, which encompasses probiotics, prebiotics and all microbiota-targeted interventions that positively impact mental health [ 138 , 140 , 141 , 142 ]. The majority of these studies primarily utilized various strains of lactobacilli and bifidobacteria as potential antidepressant probiotics.…”
Section: Approaches To Restoration Of the Gut Microbiota In Depressionmentioning
confidence: 99%